RACI Matrix Design for Managing Stakeholders in Project Case Study of PT. XYZ - Rahmad Dwi Putra Suhanda; Devi Pratami (International Journal of Innovation in Enterprise System, 2021)
Stakeholders are one of the most significant factors in the success of a project. The creation of goodteam performance in a project is caused by clear work responsibilities given to each projectstakeholder so that stakeholders have responsibility for their work and can complete their workcorrectly. The responsibility assignment matrix is a method for managing the roles of each resourceand describing the relationship between jobs for each job in the project, which is classified into fourparts, namely Responsible, Assignment, Consult, and Informed. In this paper, a matrix will bedesigned to manage the work assignments of each stakeholder involved in the case of delays in projectcompletion at PT. XYZ uses the RACI Matrix method as a guide. The results of the work assignmentmatrix design in the case study project of PT. XYZ shows that 12 stakeholders are grouped into fourclassifications according to the RACI components, which are arranged based on the level of interestand responsibility of each stakeholder to the project.